(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Informational contribution was measured by estimating abnormal returns around the release of the recommendation, while the ability to predict investment returns was analysed over a long investment horizon using the event study methodology. The study concludes that analyst recommendations, in aggregate, are useful since they enhance information availability in the market, as well as enable investors to earn abnormal returns, provided that specific trading strategies are employed to use such recommendations. Diversified portfolios formed and periodically rebalanced based on analyst recommendations, when suitably aggregated and ranked, can earn abnormal returns that are not only statistically significant, but also economically significant after reducing transaction costs. Analyst research is, however, also highly biased and can potentially mislead uninformed investors.